Mariano Iberico: aproximación a la genealogía, infancia y adolescencia de un filósofo peruano - Reyes Álvarez, Carlos (2025)
Mariano Iberico is a key figure in 20th-century Peruvian philosophy, both for his adherence to Bergsonism and for his original «philosophy of appearance». However, his biography has been little explored. This article examines previously unknown aspects of his life, from his family origins in Pataz and Chachapoyas to his childhood in Cajamarca. His family’s integration into the local elite allowed him access to a distinguished academic education. Despite an early visual impairment, Iberico excelled as a student. He completed his primary and secondary education at renowned institutions such as Colegio San Ramón and pursued three degrees at the National University of San Marcos. The analysis, based on previously unpublished documents, argues that his family, social, and educational environment played a decisive role in shaping his philosophical thought.